2023
DOI: 10.1021/acsami.3c02202
|View full text |Cite
|
Sign up to set email alerts
|

New Chemical Synthesis Strategy To Construct a Silicon/Carbon Nanotubes/Carbon-Integrated Composite with Outstanding Lithium Storage Capability

Abstract: The Si/C anode is one of the most promising candidate materials for the next-generation lithium-ion batteries (LIBs). Herein, a silicon/carbon nanotubes/carbon (Si/CNTs/C) composite is in situ synthesized by a one-step reaction of magnesium silicide, calcium carbonate, and ferrocene. Transmission electron microscopy reveals that the growth of CNTs is attributed to the catalysis of iron atoms derived from the decomposition of ferrocene. In comparison to a Si/C composite, the cycle stability of the Si/CNTs/C com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…To overcome these obstacles, researchers have employed a few methodologies, among which carbon coating is undoubtedly one of the most exemplary modification techniques. In fabricated Si/C nanocomposites, such as yolk–shell structures and core–shell structures, carbon inclusion can not only improve electrical conductivity but also effectively relieve the mechanical stress caused by volume expansion to enhance the cycle stability. ,, Although these endeavors have yielded promising results, their practical application is limited by the complex preparation process of carbon-coated nanomaterials and low yield. Additionally, carbon in Si/C nanocomposites often has lower crystallinity, conductivity, and mechanical strength, hindering its ability to achieve durable cycling performance in LIBs. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these obstacles, researchers have employed a few methodologies, among which carbon coating is undoubtedly one of the most exemplary modification techniques. In fabricated Si/C nanocomposites, such as yolk–shell structures and core–shell structures, carbon inclusion can not only improve electrical conductivity but also effectively relieve the mechanical stress caused by volume expansion to enhance the cycle stability. ,, Although these endeavors have yielded promising results, their practical application is limited by the complex preparation process of carbon-coated nanomaterials and low yield. Additionally, carbon in Si/C nanocomposites often has lower crystallinity, conductivity, and mechanical strength, hindering its ability to achieve durable cycling performance in LIBs. , …”
Section: Introductionmentioning
confidence: 99%
“…During the lithiation/delithiation processes, pure silicon materials exhibit volumetric expansion exceeding threefold, which in turn results in pulverization of the active constituents, continuous formation of solid–electrolyte interphase (SEI) film, detachment from copper foil current collectors, and ultimately leads to rapid capacity decay . Moreover, the inherent low conductivity of silicon hinders both electron and ion transport, further inhibiting its LIB performance. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNT) are also employed due to their high aspect ratio, excellent conductivity, and high mechanical strength. Encapsulation of CNT on the outer surface of Si through electrostatic self-assembly, , electrostatic adsorption, or in situ growth methods achieves a comparable effect to that of an elastic carbon layer. Researchers have also adopted a skin-like covalent encapsulation strategy to create two-dimensional covalent Si/C materials, which exhibit high stability, capacity, and rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it establishes a two-dimensional highway, facilitating the rapid transport of lithium ions (Li + ). The one-dimensional Si nanowires (SiNW) serve as the primary component for lithium storage and offer advantages in mitigating stress changes compared to bulky Si particles. , CNT plays a crucial role in enhancing electrical conductivity within the integrated electrode. , Additionally, its binding to SiNW and G helps to restrict outward expansion during SiNW alloying. When combined with cPAN, a rigid, flexible protective layer (CNT/cPAN) is formed, which extends to every corner of the integrated electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that Si compounds with carbon materials can effectively address the above issues. Carbon nanofibers (CNFs) are an ideal composite component with a high surface area, high mechanical strength, and good electrical conductivity. Si/CNF composites can not only alleviate the huge volume expansion of Si but also improve the electrical conductivity and structural stability of the composites. For instance, Bai et al synthesized Si-CNF@C composites by electrostatic self-assembly and further carbonization. CNFs and amorphous carbon can effectively improve the dispersion and contact problems of Si nanoparticles.…”
Section: Introductionmentioning
confidence: 99%